2020
DOI: 10.1111/oik.07404
|View full text |Cite
|
Sign up to set email alerts
|

Coordination in parental effort decreases with age in a long‐lived seabird

Abstract: Biparental care is widespread in avian species. Individuals may match the contribution of their partner, resulting in equal parental effort, or may exploit their partner, to minimise their own investment. These two hypotheses have received much theoretical and empirical attention in short‐lived species, that change mates between seasons. However, in species with persistent pair bonds, where divorce is rare and costly, selective pressures are different, as partners share the value of future reproduction. In suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 32 publications
0
15
0
Order By: Relevance
“…Parents may negotiate care indirectly through monitoring offspring (46)(47)(48) or directly through coordinating feeding visits or vocal communication (12,49,50). Males may also use parental care as a form of sexual signaling, if females preferentially mate with good fathers, as is found across fishes (51).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Parents may negotiate care indirectly through monitoring offspring (46)(47)(48) or directly through coordinating feeding visits or vocal communication (12,49,50). Males may also use parental care as a form of sexual signaling, if females preferentially mate with good fathers, as is found across fishes (51).…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, species with strong (stable, monogamous) bonds would have more alignment of male and female future fitness, and fathers would have more paternity certainty, leading to higher male responsiveness and lower sex differences (2,12,23,32). Alternatively, because increased male care may allow females to breed again more quickly (as seen across mammals, 33), we hypothesized that males would be more responsive than females mostly in species with strong bonds.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whether a species is more likely to cooperate or partially compensate will depend on a lot of factors (e.g. : environment, life history traits of a species, individual status such as age, social environment 46 48 ) and thus species might also vary along a continuum from being in conflict and cooperating 46 , 47 . In line with this, Lejeune et al found that in a population of blue tits, the ecological differences along an altitudinal gradient affected the pair coordination in synchrony and alternation 49 .…”
Section: Discussionmentioning
confidence: 99%
“…With the frequent occurrence of coordination among all these different seabird species, these studies altogether hint at the importance of cooperation between parents. However, they give little insight into how parental efforts are divided between the pair members as an important component, namely the foraging effort, is rarely studied in this context (but see [18,37]). Observing seabirds during their foraging trips remains difficult, meaning that important information on parental investment that occurs away from the nest is missed.…”
Section: Introductionmentioning
confidence: 99%